Agglomeration of coal and polyethylene mixtures during fixed-bed co-gasification - Igor G. Donskoy; Aleksandr N. Kozlov; Maksim V. Penzik; Denis A. Svishchev; Lu Ding (International Journal of Coal Science & Technology, 2024)
Abstract The article presents the results of experimental studies on the gasification of mixtures of brown coal and polyethylene (up to 20 wt% fraction) in a laboratory reactor. The work aims to study the agglomeration process during the heating and oxidation of the mixtures. The measurement results (gas composition, pressure drop) provide indirect information on the dynamics of thermal decomposition and structural changes in the fuel bed. We have shown that the interaction between polyethylene and a coal surface leads to the formation of dense agglomerates, in which the molten polymer acts as a binder. Clinkers form as a result of interfacial interactions between components and filtration flow rearranging. The hydrogen/carbon ratio in the solid residue of coal-polyethylene co-gasification increases from 0.07–0.2 to 1.11, indicating the formation of stable hydrocarbon compounds on the carbon surface. The conducted research makes it possible to identify possible interactions between chemical reactions and transfer processes that lead to agglomeration in mixtures of coal with polyethylene.